Models of integration of HIV and noncommunicable disease care in sub-Saharan Africa: lessons learned and evidence gaps. (1st July 2018) - Njuguna, Benson; Vorkoper, Susan; Patel, Pragna; Reid, Mike J.A.; Vedanthan, Rajesh; Pfaff, Colin; Park, Paul H.; Fischer, Lydia; Laktabai, Jeremiah; Pastakia, Sonak D.
Abstract : Objective: To describe available models of HIV and noncommunicable disease (NCD) care integration in sub-Saharan Africa (SSA). Design: Narrative review of published articles describing various models of HIV and NCD care integration in SSA. Results: We identified five models of care integration across various SSA countries. These were integrated community-based screening for HIV and NCDs in the general population; screening for NCDs and NCD risk factors among HIV patients enrolled in care; integration of HIV and NCD care within clinics; differentiated care for patients with HIV and/or NCDs; and population healthcare for all. We illustrated these models with descriptive case studies highlighting the lessons learned and evidence gaps from the various models. Conclusion: Leveraging existing HIV infrastructure for NCD care is feasible with various approaches possible depending on available program capacity. Process and clinical outcomes for existing models of care integration are not yet described but are urgently required to further advise policy decisions on HIV/NCD care integration.